Biomarkers of susceptibility and effect in car painters exposed to organic solvents (Colombia Medica, 2020)
Introduction: Car painters are routinely exposed to organic solvents classified as carcinogenic and mutagenic substances.Objective: To characterize the population susceptibility and evaluate the genotoxic effects of exposure to organic solvents.Methods: A cross-sectional study comparing a group of car painters exposed to organic solvents with a non-exposed group. CYP2E1 polymorphisms and the presence of micronuclei in lymphocytes were determined.Results: One hundred twenty-two workers participated in the study: 62 who worked in car paint shops and were exposed to solvents, and 60 who were not exposed. There were statistically significant differences between the two groups regarding micronucleated cells and nucleoplasmic bridges frequencies (p=0.042 and p=0.046, respectively; exact likelihood ratio). Significant differences were found at the interaction between the CYP2E1 genotype c1c1 and occupational exposure to solvents, with higher frequencies of micronuclei (p= 0.013) and micronucleated cells (p= 0.015). However, when the frequencies of micronuclei, micronucleated cells and nucleoplasmic bridges in the exposure group were compared between the c1c1 and c2c2/c1c2 allele groups of the CYP2E1 polymorphism, statistically significant differences were found.Conclusions: This study confirms that when workers with CYP2E1 polymorphisms, specifically the c1c1 genotype, are exposed to organic solvents, they are more likely to have somatic cell mutations, a condition associated with increased susceptibility to diseases such as cancer